Suburban planet making the world urban from the outside in - Keil, Roger 1957- (Urban futures, 2018)
"The urban century manifests itself at the peripheries. While the massive growth in urbanization is often referred to as an 'urban revolution', most of the twenty-first century's startling urban growth worldwide is happening in city peripheries. This book is about the process that creates the global urban periphery - suburbanization - and the ways of life - suburbanisms - we encounter there. Richly detailed and illustrated with examples from around the world, the book argues that suburbanization is a global process and part of the extended urbanization of the planet. This includes the gated communities of elites, the squatter settlements of the poor and many built forms and ways of life on the periphery in-between. While urbanist orthodoxy opposes low-density 'sprawl' for its disproportional environmental impact, the reality of life in the urban century is suburban: most of the earth's future 10 billion inhabitants will not live in conventional cities but in suburban constellations of one kind or another.Inspired by Henri Lefebvre's demand not to give up urban theory when the city in its classical form disappears, this book is a challenge to urban thought more generally as it invites the reader to reconsider the city from its periphery"-- Provided by publisher.